The ranger [compact disc, unabridged] - Atkins, Ace (Atkins, Ace. Quinn Colson novel., 2011)
Now an Army Ranger, he returns to a place overrun by corruption, and finds his uncle, the county sheriff, dead, a suicide, he's told, but others whisper murder. In the days that follow, it will be up to Colson to discover the truth, not only about his uncle, but about his family, his friends, his town, and not least about himself. And once the truth is discovered, there is no turning back.